70.5k views
1 vote
Find the point equidistant from the three points (-6,0),(-3,1) and (0,0).​

1 Answer

2 votes

Answer:

The point equidistant from the three points (-6,0),(-3,1) and (0,0) is (-3,-3)

Solution:

The given three points are A (-6, 0), B (–3, 1) and C (0, 0)

Let P (x, y) be the point equidistant from these three points.

Distance between two points is given as


\mathrm{D}=\sqrt{\left(\mathrm{x}_(2)-\mathrm{x}_(1)\right)^(2)+\left(\mathrm{y}_(2-) \mathrm{y}_(1)\right)^(2)}

Where
x_(1), x_(2), y_(1), y_(2) are the x and y co-ordinates

The distance between A (-6, 0) and P(x, y) is:

Using the distance formulae,


\mathrm{D}=\sqrt{(\mathrm{x}+6)^(2)+(\mathrm{y}-0)^(2)}

On taking square root we get,


D^(2)=(\mathrm{x}+6)^(2)+(\mathrm{y}-0)^(2) --- eqn 1

The distance between B(-3, 1) and P(x, y) is:


\mathrm{D}=\sqrt{(\mathrm{x}+3)^(2)+(\mathrm{y}-1)^(2)}

On taking square root we get


D^(2)=(\mathrm{x}+3)^(2)+(\mathrm{y}-1)^(2) --- eqn 2

The distance between C(x, y) and P (0, 0) is:


\mathrm{D}=\sqrt{(\mathrm{x}-0)^(2)+(\mathrm{y}-0)^(2)}


D^(2)=(\mathrm{x}-0)^(2)+(\mathrm{y}-0)^(2) -- eqn 3

By equating equation 1 = equation 2 to find the value of y


(x+6)^(2)+(y-0)^(2)=(x-0)^(2)+(y-0)^(2)

In both the expression
(\mathrm{y}-0)^(2) is common so we can cancel it.


(\mathrm{x}+6)^(2)=(\mathrm{x}-0)^(2)

On expanding we get,


x^(2)+36+12 \mathrm{x}=x^(2)

12x = -36

x = -3.

Now find the value of y using equation 3.


\begin{array}{l}{x^(2)+y^(2)=0} \\ {(-3)^(2)+y^(2)=0} \\ {3^(2)=-y^(2)} \\ {y=-3}\end{array}

Hence the required points are (-3,-3).

User Iamzozo
by
5.1k points